Dynamic mechanical behaviors of laser sintered polyurethane incorporated with mwcnts - Yuan, Shangqin (2016)
The multi-walled carbon nanotubes (MWCNTs) reinforced thermoplastic polyurethane (TPU) powders were firstly introduced into selective laser sintering system; and the systematic sintering parameters were investigated for the newly developed nanocomposite powders. The soft elastomeric behaviors of TPU composites are temperature and frequency dependent. Dynamic thermomechanical analysis was conducted to study the dynamic modulus and damping factors of laser sintered TPU nanocomposites. Laser sintered specimens exhibited the improved damping factor but the inferior storage modulus and loss modulus compared with the hotcompressed ones. The newly sintered MWCNTs/TPU composites maintain the intrinsic flexible and bendable properties of the neat TPU, and possess the improved damping resistance, which are significant factors to consider in the aerospace and automotive industries.